1992
DOI: 10.1056/nejm199204303261803
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Ganciclovir to Prevent Cytomegalovirus Disease after Heart Transplantation

Abstract: The prophylactic administration of ganciclovir after heart transplantation is safe, and in CMV-seropositive patients it reduces the incidence of CMV-induced illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
126
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(141 citation statements)
references
References 13 publications
11
126
1
1
Order By: Relevance
“…It may be related to delaying infection beyond the early posttransplant critical period, when immunosuppression requirements are greatest. The lack of effect of either prophylaxis regimen studied here in the prevention of primary infection is consistent with observations in lung transplant, pediatric liver recipients and heart recipients (25)(26)(27). In contrast, high dose oral acyclovir has been reported to be effective in preventing primary CMV infection in kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 85%
“…It may be related to delaying infection beyond the early posttransplant critical period, when immunosuppression requirements are greatest. The lack of effect of either prophylaxis regimen studied here in the prevention of primary infection is consistent with observations in lung transplant, pediatric liver recipients and heart recipients (25)(26)(27). In contrast, high dose oral acyclovir has been reported to be effective in preventing primary CMV infection in kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 85%
“…HCMV infection nearly doubles the 5-year rate of cardiac graft failure due to accelerated TVS (Grattan et al 1989) and prior to the advent of ganciclovir therapy, doubled the rate of liver graft loss at 3 years (Deotero et al 1998;Rubin 1999). In recipients of heart transplants, treatment with ganciclovir, a potent inhibitor of viral replication and CMV disease, delayed the time to allograft rejection (Merigan et al 1992). A subsequent post-hoc analysis of these data confirmed that prophylactic ganciclovir treatment delayed graft rejection compared to controls (Valantine et al 1999).…”
mentioning
confidence: 75%
“…The first report on the association of cytomegalovirus and allograft vasculopathy was by Grattan et al 30 at Stanford University. Later, other groups showed the same association and since then the pretransplantation use of ganciclovir has been proposed for prophylaxis in patients with negative serology for cytomegalovirus 31,32 . Clinical manifestation of cytomegalovirus infection may be found both in seronegative patients, the so-called primary infection, and seropositive patients, the so-called clinical reactivation.…”
mentioning
confidence: 86%